Differential aspects of the disease and treatment of Thoracic Acute Aortic Dissection (TAAD)—the European experience - Pepper, John (Annals of Cardiothoracic Surgery, 2016)
The management of patients with acute aortic dissection continues to be a challenge. It is an uncommon but lethal condition which continues to be under-diagnosed and under-treated. In this review, the term acute aortic syndrome is preferred in order to embrace the closely related pathologies of intramural hematoma (IMH) and penetrating aortic ulcer (PAU).